GASTRONOMY GENERATION Z IN BANGKA BELITUNG ISLANDS PROVINCE: EMPOWERING ENTREPRENEURIAL AWARENESS AND HALAL FOOD INNOVATION - Eka Fitriyanti; Zikri Rahmani; Ineu Sulistiana; Lasmi Hartati (As-Sidanah)
This community service program is important to empower Generation Z in Bangka Belitung. Generation Z is expected to participate actively in the rapidly growing halal culinary industry. This service aims to improve participants' knowledge and skills related to halal food innovation so that they can develop competitive businesses in local and global markets. The service's target is Generation Z in Bangka Belitung, which shows a strong interest in culinary entrepreneurship, especially in halal food and beverages. The method used in this service activity is Participatory Action Research (PAR), which includes preparation stages such as initial research and needs analysis, identification and training, location selection, and promotion and registration of participants. During the implementation, interactive training and mentoring were carried out, which focused on halal product innovation, digital marketing, and business development. The service activity results showed a significant increase in participants' understanding of the halal certification process, digital marketing techniques, and their ability to design innovative halal culinary businesses. This program contributes to the development of the capacity of young entrepreneurs, with positive implications for increasing the competitiveness of local halal products.